2014
DOI: 10.1371/journal.pone.0093141
|View full text |Cite
|
Sign up to set email alerts
|

Global Repression of Host-Associated Genes of the Lyme Disease Spirochete through Post-Transcriptional Modulation of the Alternative Sigma Factor RpoS

Abstract: Borrelia burgdorferi, the agent of Lyme disease, is a vector-borne pathogen that transits between Ixodes ticks and vertebrate hosts. During the natural infectious cycle, spirochetes must globally adjust their transcriptome to survive in these dissimilar environments. One way B. burgdorferi accomplishes this is through the use of alternative sigma factors to direct transcription of specific genes. RpoS, one of only three sigma factors in B. burgdorferi, controls expression of genes required during tick-transmis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 104 publications
1
55
0
Order By: Relevance
“…Although several studies have demonstrated that the alternative sigma factors RpoN and RpoS and other factors play key roles in the control of gene expression in Borrelia (13,40,41), additional, as-yet-unidentified regulatory factors are likely to be involved in this complex regulatory network. In many Gram-positive and Gram-negative organisms, the PEP-PTS acts as an important signal transduction system that controls gene expression depending on carbohydrate availability.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have demonstrated that the alternative sigma factors RpoN and RpoS and other factors play key roles in the control of gene expression in Borrelia (13,40,41), additional, as-yet-unidentified regulatory factors are likely to be involved in this complex regulatory network. In many Gram-positive and Gram-negative organisms, the PEP-PTS acts as an important signal transduction system that controls gene expression depending on carbohydrate availability.…”
Section: Discussionmentioning
confidence: 99%
“…One microgram of total RNA was subjected to DNase treatment as outlined in the manufacturer's protocol (Life Technologies) and used to synthesize cDNA using the High Capacity DNA Reverse Transcriptase (RT) kit (Life Technologies). A control reaction mixture lacking reverse transcriptase (no RT) was included for each cDNA synthesis reaction, and each sample was tested with three technical replicates by quantitative PCR (qPCR) using a 1:10 dilution of cDNA, the TaqMan Universal PCR Mastermix (Life Technologies), and ABI Viia7 software, as previously described (47). The constitutively expressed flaB gene was used as the PCR endogenous control to which ospC and pncA values were normalized.…”
Section: Construction Of Allelic-exchange Vectorsmentioning
confidence: 99%
“…Total RNA was extracted from B. burgdorferi cultures using TRIzol reagent, according to the manufacturer's protocol (Life Technologies, Grand Island, NY, USA), and cDNA was produced as previously described (54). Briefly, RNA was extracted by lysing spirochetes in TRIzol reagent, extracting RNA in chloroform, precipitating it in isopropanol, and resuspending it in RNase-free water.…”
Section: Methodsmentioning
confidence: 99%
“…Contaminating DNA was removed by treatment with the Turbo DNA-free kit according to the manufacturer's instructions (Life Technologies), and cDNA was produced using the high-capacity cDNA reverse transcriptase kit (Life Technologies) according to the manufacturer's instructions. Quantitative reverse transcriptase PCRs (qRT-PCRs) were performed as described previously (54) with TaqMan Universal PCR master mix (Life Technologies) and gene-specific primers and probe sets (see Table S1 in the supplemental material) (Integrated DNA Technologies, Coralville, IA, USA, or SigmaAldrich, St. Louis, MO, USA). Experiments were performed in biological and technical triplicates, and experimental results were analyzed on a Viia7 real-time PCR system with the Viia7 software package (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%